Impulsive aggression and response inhibition in attention-deficit/hyperactivity disorder and disruptive behavioral disorders: Findings from a systematic review. (July 2018) - Puiu, Andrei A.; Wudarczyk, Olga; Goerlich, Katharina S.; Votinov, Mikhail; Herpertz-Dahlmann, Beate; Turetsky, Bruce; Konrad, Kerstin
Highlights: Impulsive aggression and dysfunctional response inhibition are present in ADHD and DBDs. Broad fronto-striatal-cerebellar dysfunctions have been implicated in ADHD and DBDs. Prefrontal and cingulate cortical deficits are associated with IA in ADHD. Severe widespread cortico-subcortical breakdowns are associated with IA in DBDs. RI deficits have been attributed to hypoactivity in the lateral PFC, insula, and amygdala. Whether reduced gray matter volumes relate to ADHD and DBDs or if present as an IA epiphenomenon remains debatable. Abstract: Background: Although impulsive aggression (IA) and dysfunctional response inhibition (RI) are hallmarks of attention-deficit/hyperactivity disorder (ADHD) and disrupted behavioral disorders (DBDs), little is known about their shared and distinct deviant neural mechanisms. Aims and Methods: Here, we selectively reviewed s/fMRI ADHD and DBD studies to identify disorder-specific and shared IA and RI aberrant neural mechanisms. Results: In ADHD, deviant prefrontal and cingulate functional activity was associated with increased IA. Structural alterations were most pronounced in the cingulate cortex. Subjects with DBDs showed marked cortico-subcortical dysfunctions. ADHD and DBDs share similar cortico-limbic structural and functional alterations. RI deficits in ADHD highlighted hypoactivity in the dorso/ventro-lateral PFC, insula, and striatum, while the paralimbic system was primarily dysfunctional in DBDs. Across disorders, extensively altered cortico-limbic dysfunctions underlie IA, while RI was mostly associated with aberrant prefrontal activity. Conclusion: Control network deficits were evidenced across clinical phenotypes in IA and RI. Dysfunctions at any level within these cortico-subcortical projections lead to deficient cognitive-affective control by ascribing emotional salience to otherwise irrelevant stimuli. The clinical implications of these findings are discussed.